Challenges of students in conducting social studies research: Implications for pedagogical enhancements - Castillo, Luther; Laguerta, Margarette G. (Journal of Interdisciplinary Studies in Education, 2025)
This study examined the unique challenges faced by student-researchers in social studies, addressing the scarcity of field-focused research in the existing literature. It employs a basic qualitative design, utilizing written responses and interviews with 29 student-researchers and five faculty members for data triangulation. A reflexive thematic analysis revealed five major themes: dilemmas in topic selection and content exploration; obstacles to participant engagement and data collection; challenges in advisor and panel interactions; difficulties in the research process; and challenges to mental and physical well-being. These findings can inform improvements in research instruction, mentoring strategies, and institutional support systems. The study also highlights the importance of designing discipline-specific interventions and suggests directions for future research based on the identified limitations.